Mapping Road Capacity on Secondary Arterial Roads in Medan City Using Web-Based Geographic Information System - Septiningtiyas , Dina Tri; Samiran; Pasaribu, Hadianti Muhdinar; Mabrur, Muhammad; Efrida, Rizki; Rifq, Muhammad Ar (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
Medan City is the third largest city in Indonesia which has a population in 2022 of 2,494,512 people, with a population density of 9,413 people/km2. Based on BPS data in 2022, the number of motorized vehicles in Medan City is 288,378. One of the main problems in Medan is the existence of traffic jams. This study discusses the mapping of road capacity on secondary arterial roads in Medan City. The method used is Web GIS-based mapping which provides mapping information in digital form. The data in the study ar e traffic volume data, road geomic data, and Medan City administration maps. From the results of the study, the large road capacity in the research area was obtained namely Yos Sudarso A Road amounting to 1,485.8 smp / hour, Yos Sudarso B Road amounting to 1,485.8 smp / hour, Putri Hijau Road amounting to 1,744.2 smp / hour, Balai Kota Road amounting to 1,744.2 smp / hour, and Guru Pattimpus Road amounting to 1,679.6 smp / hour.